Green composites from vanillin‐based benzoxazine: Modified almond shell particles, curing behavior, thermal stability, mechanical properties, and stress analysis - Gorar, Athar Ali Khan; Zhiyi, Guo; Zhicheng, Wang; Daham, Abbas; Pan, Zhong‐cheng; Wang, Jun; Liu, Wen‐Bin; Derradji, Mehdi (Journal of applied polymer science, 2023)
By adhering to green chemistry principles, unique and enhanced benzoxazine composite is made from renewable vanillin and furfuryl amine. The bio‐benzoxazine poly(V‐BZF) structure was confirmed by 1 H NMR and Fourier‐transform infrared spectroscopy spectroscopy. Enhanced composites were developed successfully by blending different chemical‐treated almond shell particles with poly(V‐BZF). Differential scanning calorimetry results reveal that novel benzoxazine's curing temperature was low and slightly reduced by incorporating chemically treated fillers. The lowest polymerizing temperature was recorded as 215°C for the blend of alkali‐treated particles. Thermogravimetric analysis demonstrates that composites exhibited superior thermal characteristics, and chemical treatment positively impacts filler material. The limiting oxygen index value classifies poly(V‐BZF) composites as flame‐retardant and extinguishing. Approximately a 47.56% increase in tensile strength and a 28.9% increase in modulus were recorded with the incorporation of silane‐treated filler. Flexural tests demonstrated that composites with silane‐treated particles showed maximum flexural strength of 101.5 MPa and a modulus of 4112.6 MPa. The impact strength of composites increased to 73.3%, expanding benzoxazine's manufacturing applications. In addition, the specimen was designed to have composite properties and stress analysis was performed in two Multiphysics software packages. In all, this work confirms that adopting environmentally‐friendly methodologies and surface modification of filler can yield superior composites.